KAJIAN KEBIJAKAN PENATAUSAHAAN KAYU YANG BERASAL DARI HUTAN HAK - Epi Syahadat; Subarudi Subarudi (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2014)
Implementation of present wood administration system may not be able to guarantee the forest sustainability and improve community prosperity optimally. The objective of the policy analysis on wood administration is to explore definition, substance, regulations and effective implementation of Permenhut P. 30/2012. The method of analysis used is descriptive analysis. The results showed that wood administration from private forests include harvesting, measurement, wood species identification, wood collecting and transporting, processing and reporting. The regulation related to wood administration from private forests still has problems both in its content and substance and its field implementation. Since the issuance of Permenhut P. 30/2012, as a reference on wood administration from private forests, significant changes have been realized in the following aspects: (i) definition of private forests, (ii) objective of wood administration system, (iii) benefits for the private forest owner, (iv) the listing of wood species, (v) elimination of logging permit, and (vi) type of documents used. However, future regulation should take into consideration and anticipate new problems that may be rising such as (1) land certification of private forest, (2) incentive for officers who issue wood origin letter (SKAU), (3) monitoring of forest products and circulation,(4) controlling of log laundering from government forests, (5) competency of SKAU issuers, and (6) utilization of rubberwood from crop estate areas.